Accumulation of guanosine tetraphosphate and guanosine pentaphosphate in Myxococcus xanthus during starvation and myxospore formation. - Manoil, C (1980)
Cultures of Myxococcus xanthus develop multicellular fruiting bodies when starved for carbon and nitrogen sources on an agar surface. Under these conditions of severe starvation, cultures rapidly accumulated a compound identified as guanosine tetraphosphate by chromatographic migration of the compound and of its major acid and alkali breakdown products. The accumulation of guanosine tetraphosphate was reduced in the presence of tetracycline, indicating that it may be synthesized by mechanisms similar to those of Escherichia coli. The guanosine tetraphosphate level was also reduced in starved cultures of a mutant unable to fruit normally, although it has been determined whether the defect in guanosine tetraphosphate accumulation is responsible for the inability to fruit. Induction of spores by glycerol addition led to transient increases in both guanosine tetraphosphate and guanosine pentaphosphate at a stage following most cell shortening, but before spores had acquired full refractility.